O direito à educação como "ioiô" das políticas que ampliam a obrigatoriedade da educação básica - Antunes, Jucemara (2018)
This doctoral thesis aimed to analyze the relation between the right and the obligation to study, considering the legislation which makes compulsory the Basic Education (BE) in Brazil, since the children are 4 years old until they reach 17, and the possibilities for its legitimation in the schools run by the city and by the state of Rio Grande do Sul in Santa Maria (SM). It was chosen the qualitative approach and, with the possibility of a theoretical perspective, the cycle of policies formulated by Stephen Ball et al. (BOWE; BALL; GOLD, 1992; BALL, 1994). The research aimed to encompass the school education, which nowadays is considered mandatory by the two institutional regulatory frameworks, Constitutional Amendment number 59, from 2009 (BRAZIL, 2009a) and the Law number 12,796, (BRAZIL, 2013) , focusing on preschool and High School (HS). As locus, the schools run by the city of Santa Maria and the ones from the state of Rio Grande do Sul were considered. The relevance for the choice of the participants, among them: municipal and state managers; school administrators and teachers who work in pre-school and high school classes, it was for their importance in relation to the implementation of Law number 12,796 (BRAZIL, 2013) and its reflexes. For data collection, it was used the documentary research of the legislations that guided the expansion of schooling and semi-structured questionnaire. The analysis of the data produced was based on the Content Analysis proposed by Bardin (2011). In analyzing the relations between the right and the obligation to study, considering the current legislation and the possibilities for its legitimization in the schools run by the city and the state of Rio Grande do Sul in Santa Maria/RS, it is intended to think about the processes of a public policy in the different contexts. It is then affirmed that there is a relation of turning bills into laws instituted in the public policies which are being used now, since the Federal Constitution of 1988, when bringing the subjective public right as a way of disciplining the access to compulsory and free education. The Law number 12,796 from 2013 (BRAZIL, 2013) has extended this subjective public right, from 4 years old to 17 years old, with this relation between the right to education and compulsory schooling still remaining, which is not equivalent to guaranteeing the right of children from 4 to 5 years old to attend preschool and also from 15 to 17 years old teenagers to HS, so they also justify the title of this research " The right to education as an “yo-yo" of policies that extend the compulsory nature of Basic Education”, guaranteeing as a thesis that the public policies for Basic Education are materialized by the bias of government policies stretched out by struggles and disparities in the context of the practice and becoming more important the guarantee of the right to access than quality measures to legitimize them. Furthermore, in affirming this thesis, it is considered that it is itself subject to revision and new reinterpretations, other looks that allow further deepening, even because this is a back and forth path, and the end may be the beginning .. .